Planning and periodization in swimming: An example of a macrocycle for an adapted swimming group - Querido, A. (2009)
The planning of the training process in is commonly recognized as a fundamental aspect for the correct and harmonious development of the capacities and to improve sports results. The aim of this paper was to present an example of a macrocyle of training in a group of adapted swimmers. The group includes 5 swimmers, being 4 male and 1 female: three swimmers with Down syndrome, one swimmer with intellectual disability and one swimmer with autism. The macrocycle of training was subdivided in 23 weeks: 15 belonging to the General Preparation Period, 4 to the Specific Preparation Period, 2 to the Competitive Period, culminating with the Winter National Championships, and 2 to the Transition Period trying. At the Winter National Championships, the most important competition of this macrocycle, these swimmers obtained 7 national titles, 4 national vice-champions titles and 2 third places. These results gave the swimmers an important incentive to keep up the good work.